The unsung women of citriculture: bridging science and society through macro and micro analysis for improved technology adoption in citrus value chain - Bhattacharyya, Sangeeta; Lal, Deepa; Roy, Arnab; Lal, Priyanka; Roy, Pinaki; Sikdar, Samrat; Dutta, Suchandra; Bardhan, Tannishtha (Frontiers in Sociology, 2025)
IntroductionWomen constitute 43% of the global agricultural workforce, and remain largely undocumented in several sectors, especially citrus farming (citriculture). Although citrus fruits are cultivated commercially in more than 150 countries, significant gender disparities exist in citriculture, such as women facing drudgery, lack of access to resources, advisories, technical information, and opportunities for capacity development.MethodsIn this study, the quantum of documentation done in “science” on “women in citriculture” was analyzed through “macroanalysis” whereby bibliographic assessment and systematic review of literature of 306 articles ranging from 1929 to 2024 available in “gender and citrus farming” from 35 major citrus producing countries was done using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and Rayyan Qatar Computing Research Institute (QCRI). A cross-country visualization of gender disparities affecting agricultural technology adoption by women farmers was also done. For validating the findings with “society,” a “microanalysis” based on the theoretical grounding of Kabeer’s empowerment framework was conducted by interviewing 300 women citrus growers of Nagpur, India, on three dimensions of empowerment, namely, resources, agency, and achievements in the context of technology adoption.ResultsThe macroanalysis revealed 10 major gender disparities of 3 categories on a longitudinal and cross-sectional scale. Only 20% of respondents had a high Technology Adoption Score (4–6). Furthermore, respondents with sound technical know-how of citriculture were found to face lesser degrees of socio-personal gender disparities (t-value = 2.02, significant at the 0.05 level) than those who lacked technical knowledge.DiscussionSystematic strategies for women empowerment, based on Gender Transformative (GT) approaches, were outlined through macroanalysis. These strategies aim to enhance the impact of agricultural technologies, improve livelihoods, and promote sustainable citriculture and social development in line with the achievement of Sustainable Development Goals at microlevel. Developmental Goals achievement of Sustainable Development Goals at microlevel.